Paralympic swimming sport medicine (FINA World Sports Medicine Congress, 18, 2016)
Prof. Wayne Derman, University of Cape Town (ZAF), talks about "Paralympic Swimming Sport Medicine" at the FINA World Sports Medicine Congress 2016.